2020
DOI: 10.4093/dmj.2019.0063
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ceramide Accumulation in Podocytes by Myriocin Prevents Diabetic Nephropathy

Abstract: Background: Ceramides are associated with metabolic complications including diabetic nephropathy in patients with diabetes. Recent studies have reported that podocytes play a pivotal role in the progression of diabetic nephropathy. Also, mitochondrial dysfunction is known to be an early event in podocyte injury. Thus, we tested the hypothesis that ceramide accumulation in podocytes induces mitochondrial damage through reactive oxygen species (ROS) production in patients with diabetic nephropathy. Methods: We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Additionally, treatment with berberine improved renal injury in STZ-induced diabetic rats via downregulation of S1PR2 [ 105 ] and the use of the S1PR2 specific antagonist LTE-013 showed improved insulin resistance in human and rat hepatocytes [ 106 ], suggesting the possibility that S1PR2 inhibition may prove useful for the treatment of diabetes and its related complications. Another study demonstrated that inhibition of ceramide accumulation with myriocin in Otsuka Long Evans Tokushima fatty rats and HFD-fed mice ameliorates albuminuria and histologic features of DKD [ 107 ]. Finally, our studies demonstrated that exogenous C1P treatment or podocyte-specific inhibition of SMDP3Lb results in reduced proteinuria, improves renal outcome and restores insulin receptor signaling in diabetic db/db mice [ 6 ].…”
Section: Targeting Sphingolipids In Dkd and Fsgsmentioning
confidence: 99%
“…Additionally, treatment with berberine improved renal injury in STZ-induced diabetic rats via downregulation of S1PR2 [ 105 ] and the use of the S1PR2 specific antagonist LTE-013 showed improved insulin resistance in human and rat hepatocytes [ 106 ], suggesting the possibility that S1PR2 inhibition may prove useful for the treatment of diabetes and its related complications. Another study demonstrated that inhibition of ceramide accumulation with myriocin in Otsuka Long Evans Tokushima fatty rats and HFD-fed mice ameliorates albuminuria and histologic features of DKD [ 107 ]. Finally, our studies demonstrated that exogenous C1P treatment or podocyte-specific inhibition of SMDP3Lb results in reduced proteinuria, improves renal outcome and restores insulin receptor signaling in diabetic db/db mice [ 6 ].…”
Section: Targeting Sphingolipids In Dkd and Fsgsmentioning
confidence: 99%
“…Both endogenous and exogenous ceramides can contribute to the insulin resistance phenomenon. Previous studies reported that administration of myriocin blocked homocysteine- and high-fat diet-induced glomerular injury in the kidney 39 , 40 . In addition, palmitate exposure in cultured podocytes led to increased ceramide production 40 .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that administration of myriocin blocked homocysteine- and high-fat diet-induced glomerular injury in the kidney 39 , 40 . In addition, palmitate exposure in cultured podocytes led to increased ceramide production 40 . Inhibition of ceramide synthesis using fumonosin B1 or myriocin partially prevented palmitate-induced inhibition of glucose uptake following insulin stimulation 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Such myriocin-induced, hormesislike stress responses have been demonstrated in Caenorhabditis elegans [86] and recently Myr treatment, along with RNAi knockdown or mutation of the serine palmitoyltransferase gene, were shown to increase lifespan in C. elegans [87]. Finally, a growing body of data show that Myr treatment reduces the severity of age-related diseases in mice and rats: low dose Myr treatment lowers atherosclerosis and cardiac impairment [88][89][90][91] and reduces risk factors for metabolic syndrome, obesity, diabetes and cancer [92][93][94][95][96]. Myr also reduces amyloid beta and tau hyperphosphorylation in a mouse model of Alzheimer's disease [97] and has therapeutic effects on other neurodegenerative diseases [98,99].…”
Section: Discussionmentioning
confidence: 99%